The Impact of Hedonic, Utilitarian Value, and Perceived Quality Toward Costumer Loyalty in Cosmetic Industry - Kussudyarsana Kussudyarsana; Naisha Rahma Indraswari (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2022)
This study examined hedonic value, utilitarian value, perceived quality and customer satisfaction and their impact on consumer loyalty. Data collected used questionnaires with Likert scale 1-5 to measure respondents' responses. The sampling method used in this research was purposive sampling. Data collection was carried out on people who live in Surakarta Residency by distributing questionnaires online using Google Form. Data collection was carried out on February 15, 2021 to February 28, 2021 with a total 157 respondents. The findings of this study confirm that hedonic value has no effect on customer satisfaction and customer loyalty. Utilitarian values ​​have an influence on customer satisfaction and customer loyalty. Meanwhile, perceived quality has a direct influence on customer satisfaction and has no effect on consumer loyalty.